Employer's statutory responsibility in accordance to Occupational Safety and Health Act 1994 - Hassan, Mumtaj (Global Academic Excellence, 2018)
Law imposes responsibility on employer to provide a safe dan healty working environment to his employee. Justifiably, a workplace accident is a tragedy, which may disturb the economic development of not only an organization but a country. With that, the Occupational Safety and Health Act 1994 (OSHA) has been promulgated to ensure the safety, health and welfare of an employee in public and private sectors in Malaysia are safeguarded.Therefore, this article identifies statutory responsibility of an employer in accordance to the AKKP together with discussion on the burden of proof and prosecution against an employer for his infringement of the responsibility. In writing of this article, the writer use legal research methodology, which emphasises on doctrinal approach. At the end, recommendations are posted for a betterment of employees’ safety and health in Malaysia.